ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSANMEMBELI CAT TEMBOK MEREK DULUX PADA TOKO BERKAT PRIMA RAYA DI SANGATTA - Putra, Helman Syam (EKONOMIA, 2013)
The purpose of this study was to determine the factors that influence consumers in buying the Dulux brand paint store Sangatta Thanks to Prima Kingdom . The experiment was conducted for 3 Months ( April to June 2013 ) in Stores Thanks to Prima Kingdom Sangatta , bekaitan the factors that influence consumers' decision to buy spray paint brand Dulux in Stores Thanks to Prima Kingdom Sangatta.Kegiatan conducted research : The study of literature , field observations , interviews , documentation , data collection and analisis.Data that dikupulkan in the research include : an overview of shops , the organizational structure and the answer is responden.Peralatan analysis used multiple regression analysis with the formula : Y = a b2 X2 b1X1 b3X3 b4X4 e in where a = constant , b1 , b2 , b3 , b4 are regression coefficients , X1 = the influence of culture , X2 = social influence , X3 = personal effects , psychological effects and X4 = Y = a decision to buy . Equation Regression analysis results obtained are : Y = 1.043 0.191 ( X1 ) 0.216 ( X2 ) 0.200 ( X3 ) 0.130 ( X4 )From the calculation of the regression equation , can be described as berikut1 ) . Variable X1 ( culture ) regression coefficient = 0.191 means that each additional 1 level culture ( X1 ) will increase the buying decision variable ( Y ) was 0.191 level 2 ) . Variable X2 ( social ) coefficient regression = 0.216 means that each additional 1 level social variables ( X2 ) will increase the buying decision variable ( Y ) was 0.216 level . 3 ) . X3 ( private ) with regression coefficient = 0.200 means that each additional 1 level private variable ( X3 ) will increase the buying decision variable ( Y ) = 0.200 level 4 ) . Variable X4 ( psychological ) with regression coefficient = 0.130 means that each additional 1 level variables psychological ( X4 ) will increase the buying decision variable ( Y ) = 0.130